Cuestión de matices: el idioma de los argentinos, su ciencia y sus ancestros (sobre Borges y V.F. López) - Ennis, Juan Antonio (Universidad Nacional del Litoral, 2019)
The following pages intends to offer a preliminary approach to Vicente Fidel López’s philological attempts on the alleged Indo-European roots of the Incas’ language and culture, tracing back some of its most relevant scholarly sources, as well as depicting its material context of emergence. At the same time, a reading hypothesis is proposed, linking López’s postulates with those sketched by Jorge Luis Borges on the issue of Argentine’s own language more than half a century later. Its tentative nature notwithstanding, this approach should contribute to make visible the persisting work of some basic operations proper to the construction of constitutive bonds between languages, history and peoples.